2011
DOI: 10.1039/c0cs00215a
|View full text |Cite
|
Sign up to set email alerts
|

Copper complexes of bis(thiosemicarbazones): from chemotherapeutics to diagnostic and therapeutic radiopharmaceuticals

Abstract: The molecules known as bis(thiosemicarbazones) derived from 1,2-diones can act as tetradentate ligands for Cu(II), forming stable, neutral complexes. As a family, these complexes possess fascinating biological activity. This critical review presents an historical perspective of their progression from potential chemotherapeutics through to more recent applications in nuclear medicine. Methods of synthesis are presented followed by studies focusing on their potential application as anti-cancer agents and more re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
261
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(262 citation statements)
references
References 128 publications
1
261
0
Order By: Relevance
“…This tracer shows favorable kinetics with rapid uptake in hypoxic tissue and fast clearance from normoxic tissues, enabling imaging within 30 min after injection [66,67] . However, the exact uptake mechanism of [Cu]ATSM is still under debate [63,68,69] and several preclinical studies have shown that [Cu]ATSM uptake depends on tumor type and other characteristics than hypoxia alone [70][71][72][73][74][75][76] .…”
Section: F]fmisomentioning
confidence: 99%
See 1 more Smart Citation
“…This tracer shows favorable kinetics with rapid uptake in hypoxic tissue and fast clearance from normoxic tissues, enabling imaging within 30 min after injection [66,67] . However, the exact uptake mechanism of [Cu]ATSM is still under debate [63,68,69] and several preclinical studies have shown that [Cu]ATSM uptake depends on tumor type and other characteristics than hypoxia alone [70][71][72][73][74][75][76] .…”
Section: F]fmisomentioning
confidence: 99%
“…[Cu]ATSM is a therapeutic agent which, by replacing the Cu atom with a suitable radioactive Cu isotope, can be used for hypoxia PET imaging [63] . In nuclear medicine, Cu is of particular interest for its favorable radiochemical properties.…”
Section: F]fetnim and [mentioning
confidence: 99%
“…These qualities have led to the use of bis (thiosemicarbazones) as delivery vehicles for radioactive copper isotopes in the development of unique radiopharmaceuticals (1)(2)(3)(4). A particular focus is on the use of radiolabeled diacetylbis ð4-methylthiosemicarbazonatoÞcopper II [Cu II ðatsmÞ] (Fig.…”
Section: Radiolabeledmentioning
confidence: 99%
“…The cytotoxicity of these ligands is enhanced by coordination to metal ions such as copper, zinc, platinum and palladium. This activity is explained not only by the metals' ability to influence lipophilicity but also the mechanism of action within the cell [18][19][20][21][22][23][24][25][26]. Substitution on the C 2 position can also affect the coordination and biological properties.…”
Section: Introductionmentioning
confidence: 99%